Meningkatkan keterampilan membaca siswa melalui pendekatan literasi - Putri, Mutammimah (Maliki Interdisciplinary Journal, 2024)
The literacy approach should be used as substitute for assisting children in reading because it allows them to master the skill in a more enjoyable and meaningful way. Students will be encouraged to read texts from a variety of genres, including stories, poetry, essays, and so on, as part of literacy approach. The literacy approach will instruct children in writing skills in addition to reading. The literacy approach succeeded in improving students' reading skills. A literacy-based approach can also encourage students to read more and teach them good reading habits. Therefore, to improve students' reading skills in general, the literacy approach must be a central component in the education curriculum. The literacy approach also emphasizes improving writing skills. This is due to the fact that having strong writing skills is very important for students. The literacy approach also places great emphasis on dialogue between teachers and students. Adopting a literacy approach is essential if you want to improve the quality of learning. The effectiveness of using literacy approach can be influenced by several things. The effectiveness of the literacy approach largely depends on the teacher's aspect. The literacy approach must be implemented by teachers with the necessary knowledge and skills.